Protective role of curcumin in disease progression from non-alcoholic fatty liver disease to hepatocellular carcinoma: a meta-analysis - Li, Yubing; Deng, Xinyu; Tan, Xiyue; Li, Qianrong; Yu, Zhi; Wu, Wenbin; Ma, Xiao; Zeng, Jinhao; Wang, Xiaoyin (Frontiers in Pharmacology, 2024)
Background: Pathological progression from nonalcoholic fatty liver disease (NAFLD) to liver fibrosis (LF) to hepatocellular carcinoma (HCC) is a common dynamic state in many patients.Curcumin, a dietary supplement derived from the turmeric family, is expected to specifically inhibit the development of this progression. However, there is lack of convincing evidence.The studies published until June 2023 were searched in PubMed, Web of Science, EMBASE database and the Cochrane Library databases. The SYRCLE approach was used to evaluate the certainty of evidence. StataSE (version 15.1) and Origin 2021 software were used to analysis the critical indicators. Results: Fifty-two studies involving 792 animals were included, and three disease models were reported. Curcumin demonstrates a significant improvement in key indicators across the stages of NAFLD (Non-Alcoholic Fatty Liver Disease), liver fibrosis, and HCC (Hepatocellular Carcinoma). We conducted a detailed analysis of common inflammatory markers IL-1β, IL-6, and TNF-α, which traverse the entire disease process. The research results reveal that curcumin effectively hinders disease progression at each stage by suppressing inflammation. Curcumin exerted hepatoprotective effects in the dose range from 100 to 400 mg/Kg and treatment duration from 4 to 10 weeks. The mechanistic analysis reveals that curcumin primarily exerts its hepatoprotective effects by modulating multiple signaling pathways, including TLR4/NF-κB, Keap1/Nrf2, Bax/Bcl-2/Caspase 3, and TGF-β/Smad3. Conclusion: In summary, curcumin has shown promising therapeutic effects during the overall progression of NAFLD-LF-HCC. It inhibited the pathological progression by synergistic mechanisms related to multiple pathways including anti-inflammatory, antioxidant, and apoptosis regulation.